Molecular Basis of Methicillin and Vancomycin Resistance in Staphylococcus aureus from Cattle, Sheep Carcasses and Slaughterhouse Workers - Hanan A. Zaher; Shimaa El Baz; Abdulaziz S. Alothaim; Sulaiman A. Alsalamah; Mohammed Ibrahim Alghonaim; Abdullah S. Alawam; Mostafa M. Eraqi (Antibiotics, 2023)
Staphylococcus aureus (S. aureus) is a serious infection-causing pathogen in humans and animal. In particular, methicillin-resistant S. aureus (MRSA) is considered one of the major life-threatening pathogens due to its rapid resistance to several antibiotics in clinical practice. MRSA strains have recently been isolated in a number of animals utilized in food production processes, and these species are thought to be the important sources of the spread of infection and disease in both humans and animals. The main objective of the current study was to assess the prevalence of drug-resistant S. aureus, particularly vancomycin-resistant S. aureus (VRSA) and MRSA, by molecular methods. To address this issue, a total of three hundred samples (200 meat samples from cattle and sheep carcasses (100 of each), 50 hand swabs, and 50 stool samples from abattoir workers) were obtained from slaughterhouses in Egypt provinces. In total, 19% S. aureus was isolated by standard culture techniques, and the antibiotic resistance was confirmed genotypically by amplification nucA gen. Characteristic resistance genes were identified by PCR with incidence of 31.5%, 19.3%, 8.7%, and 7% for the mecA, VanA, ermA, and tet L genes, respectively, while the aac6-aph gene was not found in any of the isolates. In this study, the virulence genes responsible for S. aureus’ resistance to antibiotics had the highest potential for infection or disease transmission to animal carcasses, slaughterhouse workers, and meat products.